2021
DOI: 10.1093/jcag/gwab035
|View full text |Cite
|
Sign up to set email alerts
|

Living on the EDGE: Canadian Experience With EUS-directed Transgastric ERCP (EDGE) in Patients With Roux-en-Y Gastric Bypass Anatomy

Abstract: Introduction Roux-en-Y gastric bypass (RYGB) surgery imposes anatomic barriers to endoscopic retrograde cholangiopancreatography (ERCP). Potential options for biliary access in these patients include laparoscopic-assisted ERCP or balloon enteroscopy. However, these approaches require specialized equipment and/or operating room personnel and are associated with high rates of failure and adverse events compared to conventional ERCP. A recently described technique, EDGE, is an endoscopic approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Recently, Barclay et al [ 20 ] reported their experience on EDGE from Canada. They performed EDGE in 7 patients post RYGB surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Barclay et al [ 20 ] reported their experience on EDGE from Canada. They performed EDGE in 7 patients post RYGB surgery.…”
Section: Discussionmentioning
confidence: 99%